Polymer Science - Gowariker V R; Viswanathan N V; Sreedhar (Jayadev) (London New Age International Publishers, 2024)
Polymer Science deals essentially with such aspects as are of immediate concern to a new entrant to the field of polymers. Taken as a whole, these 15 chapters are aimed to raise the reader to a level from where he she can easily assimilate other specialized and exhaustive treatises on the subject. Topics dealing with chemistry, physics and technology of polymers, are developed in a careful and logical manner so as to provide an easy and enjoyable reading. Several examples and analogies are brought in so as to make the main concepts easy to follow and tables are included so that the book can serve, to a limited extent, as a handbook dealing with polymer related parameters. It is meant for students taking courses in polymer science or technology and also for those working in plastics, rubber and other allied polymer industries but without having a formal educational background in polymer science. A new Appendix D Structures of Some Common Polymers has been added in this fifth edition.
Keywords: Polymer Science